Artificial Intelligence in Medicine 14th Conference on Artificial Intelligence in Medicine, AIME 2013, Murcia, Spain, May 29 -- June 1, 2013, Proceedings - Peek, Niels; Marín Morales, Roque Luis.; Peleg, Mor.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the refereed proceedings of the 14th Conference on Artificial Intelligence in Medicine, AIME 2013, held in Murcia, Spain, in May/June 2013. The 43 revised full and short papers presented were carefully reviewed and selected from 82 submissions. The papers are organized in the following topical sections: decision support, guidelines and protocols; semantic technology; bioinformatics; machine learning; probabilistic modeling and reasoning; image and signal processing; temporal data visualization and analysis; and natural language processing.
Decision support, guidelines and protocols -- Semantic technology -- Bioinformatics -- Machine learning -- Probabilistic modeling and reasoning -- Image and signal processing -- Temporal data visualization and analysis -- Natural language processing.
Keywords: Artificial intelligence; Health informatics; Data mining; Pattern recognition; Application software; Artificial Intelligence; Health Informatics; Data Mining and Knowledge Discovery; Pattern Recognition; Information Systems Applications (incl. Internet).